Job Creation, Destruction, and Regional Employment Growth: Evidence from Korean Establishment-level Data - Jang Hee Cho; Hyun Bae Chun; Yoonsoo Lee; In Sill Yi (KDI Journal of Economic Policy, 2015)
Using the Census on Establishments collected by Statistics Korea, we analyze how the patterns of job creation and destruction differ across counties (si-gun-gu). We measure aggregate employment changes due to establishment startups, expansions, contractions, and shutdowns for each county and quantify the role of such reallocations in explaining variation in employment growth across counties. Overall we find that both rates of net entry and job creation play an important role in explaining differences in net job creation rates across regions. Moreover, counties with high employment growth rates also tend to have high exit and job destruction rates, which suggests that an active process of job reallocation is a key source of regional employment growth.
Keywords: E24; O47; R11; 330; Job Creation; Job Destruction; Entry and Exit; Regional Employment